(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
Currently, teachers of higher educational institutions use various teaching methods and techniques to solve the problem of meeting the educational needs of their students. In organic chemistry, it is important to develop students’ skills in the chemical modification of substances. Due to the different learning levels of students, some problems arise in their learning. As a solution to this problem, training using differentiated approach methods was taken as a basis. Differentiated education ensured that all studnts, regardless of their learning style, ability and background, had the opportunity to master the skills included in the curriculum and contributed to positive change in outcomes.